ANALYSIS AND TEST METHODS OF SUSPENSION STRUCTURE OF AIRBORNER MISSILE - SONG Lei; ZHANG Jin; WANG CongWei; JIN Ling; XU JunWei (Jixie qiangdu, 2019)
The suspension structure is the key bearing structure of airborne missiles. In this paper, two methods are used to analyze the strength of the suspension structure. First, the inertia release method is used. This method can accurately simulate the boundary conditions of the hang up flight but the ground static test can’t be carried out accordingly. So the boundary constraint method is put forward according to the structural characteristics of airborne missile. By comparing the numerical results of these two methods, it is found out that the boundary conditions that can meet the analytical accuracy requirements and are suitable for carrying out ground static test. Finally, ground static test was carried out accordingly. Which further validates the adaptability of the suspension structure to the flying load.